Winnie Mandela: a life - Du Preez Bezdrob, Anne Marie (Cape Town, South Africa: Zebra Press, 2003)
Everyone has an opinion about Winnie Mandela, and usually a strong one. This biography takes an in-depth and intimate look at Winnie's personal and political life, and takes the reader on a journey of understanding and traces her development from social worker, wife and mother to fiery political activist.
Keywords: Mandela, Winnie- 1936- 2018; Politician's spouses